Cardiovascular risk factors in a young adult population - Canilho, J. (2014)
Intrudution: The early identification and control of risk factors is a crucial measure to be able to act appropriately and reduce the risk of cardiovascular disease (CVD) in a population. The e_COR is a national study with a laboratory component that is being performed in the 5 Portuguese regions. The aim of the present study was to estimate the prevalence of major CVD risk factors (RF) using the data collected in the young adult population from the 3 regions already completed.